THE INFLUENCE OF TUNNELING INCENTIVE BY FOREIGN OWNERSHIP ON TRANSFER PRICING WITH TAX MINIMIZATION AND BONUS MECHANISM AS MODERATING VARIABLES (CASE STUDY ON MANUFACTURING COMPANY LISTED ON IDX IN 2017-2019) - Novia, Novia (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2020)
The increase in the company's market segment, will also impact on the company's income. This will encourage transfer pricing decision making through tunneling incentives. This study aims to determine and examine the effect of tunneling incentives on transfer pricing decisions with tax minimization and bonus mechanisms as moderating variables. The method used in this research is quantitative method. The population in this study used manufacturing companies listed in IDX from 2017-2019 with the sampling method using purposive sampling. The research data will be tested with simple linear regression and absolute difference regression using SPSS 25. The results of this study indicate that tunneling incentive has a significant negative effect on transfer pricing decisions and tax minimization and the bonus mechanism does not moderate this relationship.ReferencesChan, K., Mo, P., & Tang, T. (2015). Tax Avoidance and Tunneling: Empirical Analysis from an Agency Perspective. Journal Of International Accounting Research, 15(3), 49-66. https://doi.org/10.2308/jiar-51345Claessens, S., & Djankov, S. (1999). Ownership Concentration and Corporate Performance in the Czech Republic. Journal Of Comparative Economics, 27(3), 498-513. https://doi.org/10.1006/jcec.1999.1598Claessens, S., Djankov, S., & Lang, L. (2000). The Separation of Ownership and Control in East Asian Corporations. SSRN Electronic Journal. https://doi.org/10.2139/ssrn.206448Hartati, W. (2020). Tax Minimization, Tunneling Incentive dan Mekanisme Bonus terhadap Keputusan Transfer Pricing Seluruh Perusahaan yang Listing di Bursa Efek Indonesia. Retrieved 12 October 2020, from.Hartati, W., & Azlina, N. (2020). Analisis Pengaruh Pajak dan Mekanisme Bonus Terhadap Keputusan Transfer Pricing (Studi Empiris Pada Seluruh Perusahaan Yang Listing Di Bursa Efek Indonesia). SNA 17 Mataram, Lombok Universitas Mataram. Retrieved 12 October 2020, from.Jasmine Dwi Santosa, S., & Suzan, L. (2020). Pengaruh Pajak, Tunneling Incentive dan Mekanisme Bonus Terhadap Keputusan Transfer Pricing (Studi Kasus Pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016). Retrieved 12 October 2020, from.Klassen, K., Lisowsky, P., & Mescall, D. (2016). Transfer Pricing: Strategies, Practices, and Tax Minimization. Contemporary Accounting Research, 34(1), 455-493. https://doi.org/10.1111/1911-3846.12239Noviastika F, D., Mayowan, Y., & Karjo, S. (2020). Pengaruh Pajak, Tunneling Incentive dan Good Corporate Governance (GCG) Terhadap Indikasi Melakukan Transfer Pricing pada Perusahaan Manufaktur yang Teraftar di Bursa Efek Indonesia (Studi pada Bursa Efek Indonesia yang Berkaitan dengan Perusahaan Asing), Vol. 8 No. 1. Retrieved 12 October 2020, fromSetiawan, H. (2014). Transfer Pricing dan Risikonya Terhadap Penerimaan Negara. PPRF Kementerian Keuangan, 2- 3.Suandy, E. (2020). Perencanaan Pajak (6th ed.). Salemba Empat.Surya Saraswati, R., & Sujana, I. (2020). Pengaruh Pajak, Mekanisme Bonus, dan Tunneling Incentive pada Indikasi Melakukan Trabsfer Pricing, Vol. 19 No. 2. Retrieved 12 October 2020, from.Susanti, A., & Firmansyah, A. (2018). Determinants of transfer pricing decisions in Indonesia manufacturing companies. Jurnal Akuntansi & Auditing Indonesia, 22(2), 81-93. https://doi.org/10.20885/jaai.vol22.iss2.art1Hidayat, W., Winarso, W., Hendrawan, D. (2019). Pengaruh Pajak dan Tunneling Incentive Terhadap Keputusan Transfer Pricing Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2012-2017. Jurnal Ilmiah Akuntansi dan Manajemen (JIAM) Vol.15 No.1Jayengsari, Drivina, R., & Soetedjo, S. (2013). Pengaruh Good Corporate Governance, Kualitas Audit, Kompensasi Bonus, dan Ukuran Perusahaan terhadap Praktik Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia. Simposium Nasional Akuntansi 16 Manado.Jensen, M., & Meckling, W. (1976). Theory of The Firm:Magerial Behavior, Agency Cost and Ownership Structure. Journal of Financial Economic 3, 305-360. Mangoting, Y. (2000). Aspek Perpajakan dalam Praktek Transfer Pricing. Jurnal Akuntansi & Keuangan Vol.2 No.1.Marfuah, & Azizah, A. (2014). Pengaruh Pajak, Tunneling Incentive dan Exchange Rate pada Keputusan Transfer Pricing Perusahaan. JAAI, 157-159.Mayantya, S. (2018). Pengaruh Tax Minimization, Mekanisme Bonus, Kepemilikan Asing, Exchange Rate, dan Kualitas Audit Terhadap Keputusan Transfer Pricing. Yogyakarta: Universitas Islam Indonesia.Refgia, T. (2017). Pengaruh Pajak, Mekanisme Bonus, Ukuran Perusahaan, Kepemilikan Asing, dan Tunneling Incentive Terhadap Keputusan Transfer Pricing (Perusahaan Sektor Industri Dasar dan Kimia yang Listing di BEI Tahun 2011- 2014). JOM Fekon Vol.4 No.1.Resmi, S. (2017). Perpajakan Teori & Kasus. Indonesia: Salemba Empat.Rosa, R., Andini, R., & Raharjo, K. (2017). Pengaruh Pajak, Tunneling Incentive, Mekanisme Bonus, Debt Covenant, dan Good Corporate Governance (GCG) Terhadap Transaksi Transfer Pricing (Studi pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia tahun 2013-2015).Sarifah, D., Probowulan, D., & Maharani, A. (2019). Dampak Effective Tax Rate (ETR), Tunneling Incentive (TNC), Indeks Trend Laba Bersih (ITREND) dan Exchange Rate pada Keputusan Transfer Pricing Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia. Jurnal Ilmiah Akuntansi dan Humanika.Wafiroh, L., & Novi. (2015). Pengaruh Pajak, Tunneling Incentive, dan Mekanisme Bonus pada Keputusan Transfer Pricing Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia (BEI) Periode 2011-2013. Jurnal Universitas Islam Negeri Malang.